ChemInform Abstract: Synthesis and Characterization of Novel Aryl Cyclitols: Polycyclitols. Issue 8 (25th February 2014) - Balci, Neslihan; Anil, Baris; Kelebekli, Latif; Sahin, Ertan; Goeksu, Sueleyman
Abstract A new triol and a pentol are synthesized starting from the Diels—Alder adduct (III) via stereoselective reduction of the ketone groups in (III) and subsequent cis‐dihydroxylation, respectively.